Intramolecular acylation of α-sulfinyl carbanions. A simple preparation of 4-oxygenated spiro[4.n]alk-2-ene-1-ones - Manat Pohmakotr (2018)
A convenient synthesis of 4-hydroxy spiro[4.n]alk-2-ene-1-ones and spiro [4.n] alk-2-ene-1,4-diones, which involves the intramolecular acylation of α-sulfinyl carbanions followed by pyrolysis and/or oxidation, is described. © 1989.